THE ROLE OF NATIONAL GAMES AND THE FAMILY, SCHOOL AND COMMUNITY IN THE SPIRITUAL UPBRINGING OF CHILDREN - Abdullayev Navruz Alisher o’g’li; Ashurov Bahrom Ilkhomovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses national sports games, their benefits and importance for a healthy lifestyle. In almost all mahallas of the Republic of Uzbekistan, the state pays great attention to the spiritual development of our young people. In the mahallas, the majority of our young people are engaged in football, volleyball, basketball, handball, table tennis, athletics, national wrestling under the supervision of coaches and improve their sports skills at sports facilities.